Influence of sociodemographic factors on treatment’s choice for localized prostate cancer in Portugal - Mário Pereira-Lourenço; Duarte Vieira e Brito; João Pedro Peralta; Ricardo Godinho; Paulo Conceiçao; Mário Reis; Carlos Rabaça; Amílcar Sismeiro (Archivio Italiano di Urologia e Andrologia, 2020)
Introduction: Patients with localized prostate cancer (PCa) are active participants in the choice of treatment. Objectives: To access the effects of social and demographic factors in the choice of treatment in cases of localized PCa, in a Portuguese population. Methods: Identification of all patients with the diagnosis of localized PCa in the last four years in an oncological centre. Evaluation of the effects of sociodemographic factors (age, profession, literacy, marital status, district and number of inhabitants of the place of residence) in the choice of treatment. Results: 300 patients with localized PCa were evaluated: 17.3% (n = 52) opted for radical prostatectomy (RP); 39,3% had (n = 118) external radiotherapy; brachytherapy in 29.3% (n = 88) and other options (active surveillance, cryotherapy and hormonal therapy) in 14.1% (n = 42). In relation to surgical treatment (RP) the following results were obtained: a) > 70 years: 3.9% (n = 5); ≤ 70 years: 27.5% (n = 47), p < 0.001; b) primary sector: 10.3% (n = 3); secondary sector: 16.2% (n = 27); tertiary sector: 24.1% (n = 21); quaternary sector: 8.3% (n = 1), p = 0.296; c) marital status married: 17.9% (n = 47); single: 0% (n = 0); divorced: 25.0% (n = 5); widow: 0% (n = 0), p = 0.734; d) residency in a city: 14.1% (n = 13); city > 4000 habitants: 22.7% (n = 15); city ≤ 4000 habitants: 16.9% (n = 24), p = 0.701. Using multinomial regression with age (p = 0.001), district (p = 0.035), marital status (p = 0.027) and profession (0.179), this model explained 17.2%-28.4% of therapeutic choices (p < 0.001). Conclusions: The main socioeconomical factor that influence treatment choice was age. Unmarried patients over 70 years choose less radical prostatectomy. Other sociodemographic factors have minor influence in the choice of the treatment.